Security Policy in the Kurdistan Region - Constraints and Opportunities - Fatah, Omid Rafiq (Journal of Legal and Political Studies, 2015)
Creating a policy and working strategy in the field of security has specific importance, in particular following the changes in definition and strategies that the world has gone through in recent years. This has an impact on the different communities. If previous years has been cause for political decision makers to give importance to the field of security, the new era calls upon decision makers to revise the theories and strategies underpinning the field of security. Furthermore, work needs to be done to re-discuss questions surrounding the modern definitions and mechanisms of security to confront current obstacles facing both state and citizen security. The Kurdistan Region of Iraq already has its own well established security policy, which is tied to a number of principles that aid in the Politics surrounding the question of KRG security. These principles in turn aid the regions political decision makers to formulate independent practical policies on the ground. However, even with these underlying principles there are still numerous obstacles and challenges, of which some are topic based and others are foundational. These become major problems when attempting to layout a foundational all encompassing regional security policy. It is this reason that political decision makers in the field of KRG security must work to develop and reform the strategy of the Kurdish Region’s security forces in order to pass the current obstacles and thus establish a foundational regional security policy.
Keywords: Security Policy; Strategy; Kurdistan Region; Iraq; KRG Security